HUBUNGAN ANTARA PSYCHOLOGICAL CAPITAL DENGAN WORK ENGAGEMENT PADA KARYAWAN PT. BANK MEGA REGIONAL AREA SEMARANG - Nugroho, Dwi Ari Setyo; Mujiasih, Endah; Prihatsanti, Unika (Jurnal Psikologi, 2013)
This study aimed to assess the relationship between psychological capital with work engagement employees of PT. Bank Mega Regional Area Semarang. Psychological capital is an individual’s positive psychological state of development and is characterized by self- efficacy, optimism, hope and resiliency. Then, work engagement is defined as a positive, fulfilling, work-related state of mind that is characterized by vigor, dedication, and absorption. This study used proportional sampling technique. The subjects were all employees of PT. Bank Mega Regional Area Semarang which have staff levels (N=73). The research instrument was psychological capital scales with 28 items (α = 0.953) and work engagement scales with 29 items (α = 0.938). The results by simple regression analysis obtained rxy = 0.716, with p value = 0.000 (p <0.05). The results indicated that there was a positive correlation between psychological capital and work engagement. The higher psychological capital was higher work engagement. Coefficient of determination by 51,3, it meaning that psychological capital effectively contributed for 51,3 % of work engagement. The remaining 48,7 % determined by other factors that are not revealed in this study, for example: job resources and job demands.Keywords: Psychological capital, work engagement, employee